Integration of Islamic Concept in Teaching Biology at the University - Sari, Ajid M. (HM Publisher, 2022)
Biological science that is taught in most learning institutions has been secular in nature. Almost all of the biological processes, theories and principles are taught without referring to Islamic concept. The biological Science teachers need to apply and integrate the Islamic context in teaching biology in order that biological teaching in the university will be accepted under Islamic view, and biological teaching of Islam becomes part of the curriculum. This study aimed to describe the Islamic concept of teaching biology in Mindanao State University, Sulu, Philippines. This study is an observational descriptive study. The respondents were the biology teachers and students and other faculty members of Mindanao State University, Sulu, where this study was conducted. A set of questionnaires were the research data gathering instruments. The questionnaire was composed of three major parts: relevance of Qur’anic verses and biological concept, integration of Islamic context in the curriculum and awareness and perception toward integration of Islamic concept. The results stated most of the respondents are aware and have agreed on the relevance of biological and Islamic concepts. Therefore, integration of Islamic concept in teaching biology is necessary and the verses must be cited for recasting the biological concepts, theories and principles to avoid misconception on Islamic and biological science concepts.